Major postharvest fungal diseases of papaya cv. 'Sekaki' in Selangor, Malaysia - Rahman, Muklesur A.; Tengku Muda Mohamed, Mahmud; Kadir, Jugah; Abdul Rahman, Russly; Begum, Most Mahbuba (Universiti Putra Malaysia Press, 2008)
A total of seven fungi were identified from the surface of fully matured papaya fruits cv. 'Sekaki' collected form two different fields namely University Agriculture Park, UPM and MARDI, Selangor and a fruit exporter [Seng Chew Hup Kee (M) Sdn Bhd, Kajang, Selangor, Malaysia]. They were identified as Botryodiplodia theobromae, Colletotrichum capsici, C. gloeosporioides, Fusarium sp., Phomopsis sp., Rhizopus stolonifer and Stemphylium sp.. Among the diseases, the highest incidence ranged from 90 to 98% and severity of 25 to 38% were recorded for anthracnose caused by C. gloeosporioides for all three sources, followed by stem-end-rot caused by Botryodiplodia theobromae. Pathogenicity test showed that both wounded and unwounded fruits inoculated with conidial suspension of C. gloeosponoides developed distinct symptoms of anthracnose after three and five days of inoculation, respectively.